2015
DOI: 10.1016/j.ophtha.2014.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography for the Monitoring of Neovascular Age-Related Macular Degeneration

Abstract: There is substantial disagreement between OCT and FFA findings in detecting active disease in patients with nAMD who are being monitored. Both methods may be needed to monitor patients comprehensively with nAMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 23 publications
3
29
0
2
Order By: Relevance
“…1 Specifically, the introduction of the high-resolution spectral-domain OCT allows for delineation of retinal layers and differentiation of retinal structures in choroidal neovascularization. 2 Age-related macular degeneration is one of the major causes of permanent blindness in people older than 65 years worldwide and its incidence rate continues to increase.…”
mentioning
confidence: 99%
“…1 Specifically, the introduction of the high-resolution spectral-domain OCT allows for delineation of retinal layers and differentiation of retinal structures in choroidal neovascularization. 2 Age-related macular degeneration is one of the major causes of permanent blindness in people older than 65 years worldwide and its incidence rate continues to increase.…”
mentioning
confidence: 99%
“…An important question is whether angiography is actually needed and to what extent can OCT replace fluorescein angiography and ICGA in AMD. 22,23 A recent study found that OCT, despite being safer, more convenient, and less costly, cannot totally replace FA because there is a substantial disagreement between OCT and FA findings in detecting active disease in patients with neovascular AMD who are being monitored, and that both modalities may be needed to comprehensively monitor patients. 23 The primary reason for the current trend of increasing use of OCT and decreasing use of FA and ICGA in clinical practice is the noninvasiveness and rapid acquisition provided by the former technology in comparison to the opposite for the latter.…”
mentioning
confidence: 99%
“…• Note: A series of, for example, three injections can be preplanned so that the follow-up visits are carried out after the series of injections o In monitoring the activity of the disease, OCT may be rather sensitive compared to FA in discovering an active disease, but the specificity of OCT may be acceptable at best (Castillo et al 2015).…”
Section: Follow-upmentioning
confidence: 99%